ANALISIS KEMAMPUAN PENALARAN MATEMATIS KELAS 4 SEKOLAH DASAR DITINJAU DARI KEMAMPUAN BERPIKIR - tahriza, fitra nabila; Muna, Fauzul; Lulu Widiyant, Alfiana; Farokhah, Innalatul; Berliana Fitri, Navandra (AL KHAWARIZMI: Jurnal Pendidikan Matematika, 2025)
Low mathematics scores are related to students' reasoning abilities. The reasoning process is very important to train in students to train their thinking development abilities, especially in solving problems. This research aims to analyze mathematical reasoning abilities in terms of thinking abilities in grade 4 elementary school students. The research subjects were 4th grade students at SD N 3 Kandangmas, Kudus, totaling 4 students with the highest scores in each indicator of mathematical reasoning using a purposive sampling technique. The instruments used in this research were an interview sheet and essay questions consisting of 4 questions with flat shapes and indicators. The research results show that students' mathematical reasoning abilities in solving mathematical reasoning-based problems at school are quite sufficient. Of the 4 indicators, 2 indicators can be fulfilled correctly and well, 1 indicator has not been fulfilled properly, and 1 indicator has not been fulfilled.